Dissolution kinetics of ulexite with CO2 in methanol medium - Ozekmekci, Mehtap; Copur, Mehmet (Taylor & Francis Ltd, 2025)
In this study, the reaction kinetics of ulexite with CO2 in methanol were investigated in a pressurised reactor for the synthesis of trimethyl borate (TMB). The experimental parameters were varied as follows: temperature (T), 40-100 degrees C; solid-to-liquid ratio (SL), 0.05-0.2 g/mL; reaction time (t), 10-120 min; pressure (P), 10-30 bar; particle size (PS) 63-180 mu m; stirring speed (SS), 500-750 rpm. The results indicated that the dissolution rate increased with higher reaction temperatures and pressures, but decreased with larger particle sizes and higher solid to liquid ratio. However, stirring speed had no significant effect on the dissolution rate. It was observed that CaCO3 crystals that formed on the surface of the solid during the reaction, inhibiting the dissolution of the mineral. Calcium carbonate was produced in the aragonite phase without the use of additives. Thus, a method has been proposed to utilise CO2 and sequester it in a stable and permanent manner. In this study, a novel production process for trimethyl borate (TMB) was investigated, and the reaction mechanism was elucidated. A comprehensive analysis of the reaction mechanism related in the TMB synthesis process were obtained. For kinetic analysis, various empirical models were applied to fit the experimental data. Scanning Electron microscopy (SEM) and X-Ray diffraction (XRD) analyses were performed on the solid sample remaining after dissolution, and the results were supported by statistical analysis. The reaction rate was found to best described by the Avrami model. The activation energy of this process was calculated as 21 kJ/mol. Dans cette & eacute;tude, on a examin & eacute; la cin & eacute;tique de r & eacute;action de l'ulexite avec du CO2 dans le m & eacute;thanol, dans un r & eacute;acteur sous pression, pour la synth & egrave;se du borate de trim & eacute;thyle (TMB). Les param & egrave;tres exp & eacute;rimentaux variaient comme suit: temp & eacute;rature (T), 40 & agrave; 100 degrees C; rapport solide/liquide (SL), 0.05 & agrave; 0.2 g/ml; temps de r & eacute;action (t), 10 & agrave; 120 min; pression (P), 10 & agrave; 30 bar; taille des particules (PS), 63 & agrave; 180 mu m; vitesse d'agitation (SS), 500 & agrave; 750 tr/min. Les r & eacute;sultats ont indiqu & eacute; que le taux de dissolution augmentait avec des temp & eacute;ratures et des pressions de r & eacute;action plus & eacute;lev & eacute;es, mais diminuait avec des tailles de particules plus grandes et un rapport solide/liquide plus & eacute;lev & eacute;. Cependant, la vitesse d'agitation n'avait pas d'effet significatif sur le taux de dissolution. On a observ & eacute; que des cristaux de CaCO3, form & eacute;s & agrave; la surface du solide pendant la r & eacute;action, inhibaient la dissolution du min & eacute;ral. Du carbonate de calcium & eacute;tait produit dans la phase aragonite sans utilisation d'additifs. Ainsi, on a propos & eacute; une m & eacute;thode pour utiliser le CO2 et le s & eacute;questrer de mani & egrave;re stable et permanente. Dans cette & eacute;tude, on a examin & eacute; un nouveau proc & eacute;d & eacute; de production de borate de trim & eacute;thyle (TMB), et l'on a & eacute;lucid & eacute; le m & eacute;canisme de r & eacute;action. On a obtenu une analyse compl & egrave;te du m & eacute;canisme de r & eacute;action reli & eacute; au proc & eacute;d & eacute; de synth & egrave;se du TMB. Pour l'analyse cin & eacute;tique, on a appliqu & eacute; diff & eacute;rents mod & egrave;les empiriques pour ajuster les donn & eacute;es exp & eacute;rimentales. On a effectu & eacute; des analyses par microscopie & eacute;lectronique & agrave; balayage (MEB) et par diffraction des rayons X (XRD) sur l'& eacute;chantillon solide restant apr & egrave;s la dissolution, et les r & eacute;sultats ont & eacute;t & eacute; & eacute;tay & eacute;s par une analyse statistique. On a trouv & eacute; que le mod & egrave;le d'Avrami d & eacute;crivait le mieux le taux de r & eacute;action. On a calcul & eacute; l'& eacute;nergie d'activation de ce proc & eacute;d & eacute; & agrave; 21 kJ/mol.
Keywords: Ulexite; dissolution; kinetics; methanol; carbon dioxide